Forever Minus a Day: A Consideration of Copyright Term Extension in South Africa - Rens, Andrew; Lessig, Lawrence (My University, 2006)
The European Union and the United States have extended their copyright terms from the life of the author plus 50 years to life plus 70 years. They now press a similar extension on developing nations. Term extension has significant costs, especially for developing nations. These costs require careful consideration. One way to significantly reduce these costs is to require registration for the benefit of term extension.